Perencanaan Sistem Penyediaan Air Bersih di Kampung Waibron Distrik Sentani Barat Kabupaten Jayapura Provinsi Papua - Abrauw, Alberth E S; Wenda, Tepi (Universitas Pahlawan Tuanku Tambusai, 2025)
At this time the problem that occurs in Waibron Village is the utilization of groundwater as a source of clean water for daily consumption, while there are 3 surface water sources that have the potential as raw water sources. Thus, it is necessary to utilize existing water sources, therefore it is necessary to plan a clean water supply system by utilizing raw water sources, namely Waibron river water. Thus, the objectives of the study were to determine the characteristics of Waibron river water, the water needs of the Waibron Village community and plan a clean water supply system. The type of research is descriptive by measuring the quality and quantity of raw water. Planning is carried out by planning the water needs of the Waibron Village community for 20 years of planning, namely 2021-2041, water quality based on laboratory tests shows that the physical and chemical parameters are still below the quality standards, while the total coliform microbiological parameters are 2 MPN/100 ML which exceeds the quality standards based on PERMENKES No.32 of 2017. Based on the calculation of raw water quantity, it is 13.392 liters / second or 1,157,068, 8 liters / day. With the total water demand of Waibron Village, namely 741,762 liters / day in 2041, the current amount of water discharge can meet domestic and non-domestic needs. In the planning of the clean water supply system unit, it is determined that the free channel Intake has dimensions of 54 m3, a sedimentation unit with dimensions of 52.4 m3, a 20 liter chlorination basin, a 242 m3 dimensioned reservoir. The planned piping system uses HDPE type pipes with dimensions in 4 inch transmission pipes and 2 ½ inch distribution pipes and 0.5 inch SR pipes. In the process of distributing clean water, simulations are carried out using the Epanet 2.0 program and the average remaining pressure on the pipe network is ± 10 m so that the flow can be fulfilled in 24 hours of distribution.